High-stability rare earth-containing six-component low-resistance high-B-value NTC thermosensitive ceramic material and preparation method thereof
Patent Information
- Application Number
- CN202611160630.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-08-03
AI Technical Summary
引入铜元素可有效降低电阻率,但同时铜掺杂带来严重的稳定性劣化,容易出现老化值大幅提高的现象,且阻值漂移远超可接受范围,严重影响了该类材料的实际应用效果,其主要原因在于铜离子价态转变及离子空位迁移导致电学性能失稳
1、本申请所制得最终的热敏陶瓷材料,成功打破了传统NTC热敏陶瓷材料中电阻率与B值相互制约的技术瓶颈,实现了低阻值与高灵敏度的良好统一,显著提升了温度检测的精确性和响应速度;同时,材料在高温贮存、湿热环境及冷热冲击等苛刻服役条件下的长期稳定性得到大幅改善,阻值漂移得到有效抑制,能够满足汽车电子、工业控制和新能源电池管理系统等高可靠性场景对温度传感器长期精密监测的严苛要求,应用效果优异且应用前景广泛。
Smart Images

Figure CN122647212B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of thermistor ceramic materials, and in particular to a high-stability, rare-earth-containing six-component, low-resistivity, high-B-value NTC thermistor ceramic material and its preparation method. Background Technology
[0002] Negative temperature coefficient (NTC) thermistor ceramics are widely used in temperature measurement, control, and compensation due to their high accuracy, interchangeability, and reliability, covering scenarios such as consumer electronics, automotive electronics, industrial control, and IoT terminals. Currently, commercially available NTC materials are typically composed of manganese-based spinel oxides, and their electrical properties are controlled by the type and proportion of transition metal ions. However, these materials generally exhibit a positive correlation between room-temperature resistivity and the material constant B value; that is, a higher resistivity results in a higher B value and ideal sensitivity, but reducing resistivity often leads to a simultaneous decrease in the B value, significantly degrading sensitivity and making it difficult to meet the application requirements of both low resistivity and high sensitivity.
[0003] To address this technical challenge, researchers have attempted to dope or composite with other oxides. Introducing copper can effectively reduce resistivity, but copper doping also leads to severe stability degradation, resulting in a significant increase in resistivity over time, with resistance drift far exceeding acceptable limits. This severely impacts the practical application of such materials, primarily due to the instability of electrical properties caused by copper ion valence state transitions and ion vacancy migration. Furthermore, while composite materials prepared by combining copper with low-resistivity oxide phases offer some improvement, the atoms of the two phases easily dissolve into each other during high-temperature sintering, causing component segregation and poor microstructure uniformity and consistency, making them unsuitable for widespread application.
[0004] In summary, the main technical problems of existing technologies include: 1. Traditional spinel systems struggle to achieve both low resistivity and high Brønsted-B (B-value). As resistivity decreases, the B-value drops, leading to insufficient sensitivity. While copper doping can reduce resistivity, it severely degrades aging stability, failing to meet long-term reliability requirements. 2. Composite modification methods suffer from poor stability and consistency due to solid solution and segregation issues. Therefore, there is an urgent need to develop a novel NTC thermistor ceramic material and its preparation method that can achieve both low resistivity and high B-value while possessing excellent long-term stability. Summary of the Invention
[0005] To address the aforementioned issues, this application provides the following technical solutions: A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material, by mass percentage, comprises: 8-22% manganese tetroxide, 18-37% nickel oxide, 7-22% reinforcing material, 0.1-1% lanthanum trioxide, 1.5-4% combined functional material, and cobalt tetroxide to make up the balance to 100%.
[0006] In a preferred embodiment, the mass ratio of manganese tetroxide, nickel oxide, and lanthanum trioxide is (12~20):(28~36):(0.1~0.45).
[0007] In a preferred embodiment, the mass ratio of manganese tetroxide, nickel oxide, and lanthanum trioxide is (12~18):(29~35):(0.12~0.41).
[0008] In a preferred embodiment, the D50 particle size of the manganese tetroxide is 1~3μm.
[0009] In a preferred embodiment, the D50 particle size of the manganese tetroxide is 1~2μm.
[0010] In a preferred embodiment, the D50 particle size of the nickel oxide is 1.5~2.5μm.
[0011] In a preferred embodiment, the D50 particle size of the nickel oxide is 1.5~2μm.
[0012] In a preferred embodiment, the reinforcing material is a combination of nano-copper oxide and nano-zinc oxide.
[0013] In a preferred embodiment, the mass ratio of the nano-copper oxide to the nano-zinc oxide is (1.5~4.5):(7.5~13).
[0014] In a preferred embodiment, the mass ratio of the nano-copper oxide to the nano-zinc oxide is (2~3.5):(7.8~11.1).
[0015] In a preferred embodiment, the D50 particle size of the nano-copper oxide is 30~80nm.
[0016] In a preferred embodiment, the D50 particle size of the nano-copper oxide is 30~50nm.
[0017] In a preferred embodiment, the D50 particle size of the nano zinc oxide is 20~60nm.
[0018] In a preferred embodiment, the D50 particle size of the nano zinc oxide is 20~40nm.
[0019] In a preferred embodiment, the mass ratio of manganese tetroxide, reinforcing material, and combined functional material is (12~20):(9.5~15.5):(1.5~3.5).
[0020] In a preferred embodiment, the mass ratio of manganese tetroxide, reinforcing material, and combined functional material is (12~18):(9.8~14.5):(1.6~2.8).
[0021] This application uses a manganese-cobalt-nickel ternary spinel system as the matrix and achieves a performance balance between low resistivity and high B-value through the combined effect of multiple dopants. The introduction of nano-copper oxide optimizes the transition path of charge carriers between octahedral sublattices, thereby effectively reducing room temperature resistivity. At the same time, nano-zinc oxide effectively changes the bonding state and electron cloud distribution of neighboring ions, improving the material's sensitivity to temperature changes and significantly increasing the B-value. These two approaches optimize performance from two directions, avoiding performance imbalances caused by single doping and effectively resolving the contradiction between resistivity and B-value. On this basis, rare-earth lanthanum trioxide further improves grain boundary defects and suppresses cation redistribution during high-temperature sintering and use, providing a fundamental basis for the material's structural stability.
[0022] In a preferred embodiment, the D50 particle size of the lanthanum trioxide is 2~5μm.
[0023] In a preferred embodiment, the D50 particle size of the lanthanum trioxide is 2.5~4μm.
[0024] In a preferred embodiment, the combined functional material is a combination of bismuth oxide, samarium oxide, and tantalum oxide.
[0025] In a preferred embodiment, the mass ratio of bismuth oxide, samarium oxide and tantalum oxide is (5~7):(1.5~3):(0.8~1.4).
[0026] In a preferred embodiment, the mass ratio of bismuth oxide, samarium oxide and tantalum oxide is (5.5~6.5):(2~2.5):(1~1.2).
[0027] In a preferred embodiment, the D50 particle size of the bismuth oxide is 1~5μm.
[0028] In a preferred embodiment, the D50 particle size of the bismuth oxide is 1~3μm.
[0029] In a preferred embodiment, the D50 particle size of the samarium oxide is 1~3μm.
[0030] In a preferred embodiment, the D50 particle size of the samarium oxide is 1~2μm.
[0031] In a preferred embodiment, the D50 particle size of the tantalum oxide is 0.5~2μm.
[0032] In a preferred embodiment, the D50 particle size of the tantalum oxide is 0.5~1.1μm.
[0033] This application introduces a composite agent consisting of bismuth oxide, samarium oxide, and tantalum oxide to address the long-term stability degradation caused by copper doping. During sintering, bismuth oxide not only promotes intergranular mass migration and ceramic densification but also provides favorable conditions for the uniform distribution of subsequent dopants by wetting grain boundaries. The addition of samarium oxide, with its larger ionic radius, effectively increases the activation energy required for copper ion valence transitions and vacancy migration. Tantalum oxide, on the other hand, generates a strong electrostatic pinning effect, suppressing the directional drift of mobile ions over a long scale. The combined effect of these three agents significantly enhances the material's resistance to performance degradation under thermal and electrical stress without affecting the overall electrical properties, thereby achieving excellent reliability in various environments.
[0034] In a preferred embodiment, the D50 particle size of the cobalt tetroxide is 0.8~2.5μm.
[0035] In a preferred embodiment, the D50 particle size of the cobalt tetroxide is 0.8~1.4μm.
[0036] A method for preparing the above-mentioned high-stability rare-earth-containing six-component low-resistivity, high-B-value NTC thermistor ceramic material specifically includes the following steps: S1: All weighed raw materials are put into a high-speed pulverizer for dry grinding, and the ground and mixed powder is placed in a sagger and pre-fired at a temperature of 900~1100℃ in air atmosphere; S2: The pre-fired powder is poured into a planetary ball mill and wet ball milled using deionized water as the ball milling medium, and dried after ball milling to obtain ceramic powder; S3: The dried ceramic powder is filled into a mold. In the process, the blank is first pre-pressed using a dry press to obtain a preliminary blank. Then, the preliminary blank is placed in a rubber sleeve and vacuum-sealed. It is then placed in a cold isostatic press and cold isostatically pressed to obtain an ingot. S4: The ingot is placed in a high-temperature sintering furnace and fired at a temperature of 1100~1300℃. After being cooled to room temperature in the furnace, a sintered block is obtained. The sintered block is cut into thin slices using a precision inner circle cutter. Both sides of the thin slices are evenly coated with silver electrode paste and placed in a roller kiln for silver firing. After completion, the thin slices are cut into slices according to specifications using a precision dicing machine to obtain NTC thermistor ceramic material.
[0037] The preferred embodiment of the preparation method of the high-stability rare-earth-containing six-component low-resistivity high-B-value NTC thermistor ceramic material specifically includes the following steps: S1: All weighed raw materials are put into a high-speed pulverizer for dry grinding at a speed of 30,000-32,000 rpm for 1-3 minutes. The ground and mixed powder is placed in a sagger and pre-fired at 900-1100℃ in air atmosphere for 3-5 hours; S2: The pre-fired powder is poured into a planetary ball mill and wet-milled using deionized water as the milling medium at a speed of 200-300 rpm for 6-8 hours. After the milling is completed, the slurry is removed and dried in an oven at 100-110℃ to obtain ceramic powder; S3: The dried ceramic powder is filled into a mold and first pressed using a dry press at 5... Pre-pressing is performed at 0~80MPa to obtain a preliminary billet. The preliminary billet is then placed in a rubber sleeve and vacuum-sealed. It is then placed in a cold isostatic press and cold isostatically pressed at 250~300MPa to obtain an ingot. S4: The ingot is placed in a high-temperature sintering furnace and fired at 1100~1300℃ for 8~10 hours. It is then cooled to room temperature with the furnace to obtain a sintered block. The sintered block is cut into thin slices with a thickness of 450~460μm using a precision inner circle cutter. Both sides of the thin slices are uniformly coated with silver electrode paste and placed in a roller kiln for silver firing. The inner belt speed of the roller kiln is 60~90mm / min, the maximum silver firing temperature is 780~900℃, and the total firing time is 320~400min. After completion, the thin slices are cut into pieces according to specifications using a precision dicing machine to obtain the NTC thermistor ceramic material.
[0038] Beneficial effects of the application plan: 1. The final thermistor ceramic material obtained in this application successfully breaks through the technical bottleneck of the mutual constraint between resistivity and B value in traditional NTC thermistor ceramic materials, achieving a good balance between low resistance and high sensitivity, and significantly improving the accuracy and response speed of temperature detection. At the same time, the long-term stability of the material under harsh service conditions such as high-temperature storage, humid and hot environment and thermal shock is greatly improved, and resistance drift is effectively suppressed. It can meet the stringent requirements of long-term precise monitoring of temperature sensors in high-reliability scenarios such as automotive electronics, industrial control and new energy battery management systems. The application effect is excellent and the application prospects are broad.
[0039] 2. This application uses a manganese-cobalt-nickel ternary spinel system as the matrix and achieves a performance balance between low resistivity and high B-value through the synergistic effect of multiple dopants. The introduction of nano-copper oxide optimizes the transition path of charge carriers between octahedral sublattices, thereby effectively reducing room temperature resistivity. Simultaneously, nano-zinc oxide enhances the material's sensitivity to temperature changes, significantly increasing the B-value. These two approaches optimize performance from two directions, effectively resolving the contradiction between resistivity and B-value. Furthermore, rare-earth lanthanum trioxide further improves grain boundary defects, providing a fundamental basis for the material's structural stability.
[0040] 3. This application introduces a composite agent composed of bismuth oxide, samarium oxide and tantalum oxide. The three work together to promote intergranular material migration and ceramic densification, increase the activation energy required for copper ion valence state transformation and vacancy migration, and suppress the directional drift of mobile ions on a long scale. The three work together to significantly enhance the material's ability to resist performance degradation under thermal and electrical stress without affecting the main electrical properties, thereby achieving excellent multi-environment reliability. Attached Figure Description
[0041] Figure 1 This is a physical SEM image of the high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material prepared in Example 1 of this application.
[0042] Figure 2 SEM image of the high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material prepared in Example 2 of this application.
[0043] Figure 3 SEM image of the high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material prepared in Example 3 of this application. Detailed Implementation
[0044] Example 1 A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material, by mass percentage, comprises: 12% manganese tetroxide, 35% nickel oxide, 9.88% reinforcing material, 0.12% lanthanum trioxide, 1.95% combined functional material, and cobalt tetroxide to make up the balance to 100%.
[0045] The D50 particle size of manganese tetroxide is 1.8 μm; the D50 particle size of nickel oxide is 1.6 μm.
[0046] The reinforcing material is a combination of nano-copper oxide and nano-zinc oxide in a mass ratio of 2:7.88; the D50 particle size is 45nm; and the D50 particle size of the nano-zinc oxide is 25nm.
[0047] The D50 particle size of lanthanum trioxide is 2.8 μm.
[0048] The combined functional material is a combination of bismuth oxide, samarium oxide and tantalum oxide in a mass ratio of 6:2.3:1.2.
[0049] The D50 particle size of bismuth oxide is 2 μm; the D50 particle size of samarium oxide is 1.2 μm; and the D50 particle size of tantalum oxide is 0.8 μm.
[0050] The D50 particle size of cobalt tetroxide is 1 μm.
[0051] A method for preparing the above-mentioned high-stability rare-earth-containing six-component low-resistivity, high-B-value NTC thermistor ceramic material includes the following steps: S1: All weighed raw materials are put into a high-speed pulverizer for dry grinding at a speed of 30,000 rpm for 1.5 min. The ground and mixed powder is placed in a sagger and pre-fired at 1000℃ in air atmosphere for 4 h; S2: The pre-fired powder is poured into a planetary ball mill and wet-milled using deionized water as the milling medium at a speed of 250 rpm for 6 h. After the milling is completed, the slurry is removed and dried in a 100℃ oven to obtain ceramic powder; S3: The dried ceramic powder is filled into a mold and first pressed using a dry press. Pre-pressing at 60MPa yields a preliminary billet, which is then placed in a rubber sleeve, vacuum-sealed, and placed in a cold isostatic press at 300MPa to form an ingot. S4: The ingot is placed in a high-temperature sintering furnace and fired at 1200℃ for 8 hours. After cooling to room temperature in the furnace, a sintered block is obtained. The sintered block is then cut into thin slices with a precision inner circle cutter, each slice being 460μm thick. Both sides of the thin slices are uniformly coated with silver electrode paste and placed in a roller kiln for silver firing. The inner belt speed of the roller kiln is 70mm / min, the maximum silver firing temperature is 850℃, and the total firing time is 360min. After completion, the thin slices are diced according to specifications using a precision dicing machine to obtain the NTC thermistor ceramic material.
[0052] The SEM image of the high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material prepared in this embodiment is shown below. Figure 1 As shown.
[0053] Example 2 A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material differs from Example 1 in that, by mass percentage, its raw material scheme includes: 16% manganese tetroxide, 31% nickel oxide, 11.77% reinforcing material, 0.23% lanthanum trioxide, 2% combined functional material, and cobalt tetroxide to make up the balance to 100%.
[0054] The reinforcing material is a combination of nano-copper oxide and nano-zinc oxide in a mass ratio of 2.5:9.27.
[0055] The SEM image of the high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material prepared in this embodiment is shown below. Figure 2 As shown.
[0056] Example 3 A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material differs from Example 1 in that, by mass percentage, its raw material scheme includes: 18% manganese tetroxide, 29% nickel oxide, 14.59% reinforcing material, 0.41% lanthanum trioxide, 2.2% combined functional material, and cobalt tetroxide to make up the balance to 100%.
[0057] The reinforcing material is a combination of nano-copper oxide and nano-zinc oxide, with a mass ratio of 3.5:11.09.
[0058] The SEM image of the high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material prepared in this embodiment is shown below. Figure 3 As shown.
[0059] Comparative Example 1 A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material differs from Example 1 in that, by mass percentage, its raw material scheme includes: 25% manganese tetroxide, 22% nickel oxide, 9.88% reinforcing material, 0.58% lanthanum trioxide, 1.95% combined functional material, and cobalt tetroxide to make up the balance to 100%.
[0060] Comparative Example 2 A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material differs from Example 1 in that, by mass percentage, its raw material scheme includes: 10% manganese tetroxide, 40% nickel oxide, 9.88% reinforcing material, 0.22% lanthanum trioxide, 1.95% combined functional material, and cobalt tetroxide to make up the balance to 100%.
[0061] Comparative Example 3 A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material differs from Example 1 in that the combined functional material is a combination of samarium oxide and tantalum oxide in a mass ratio of 4:3.
[0062] Comparative Example 4 A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material differs from Example 1 in that the combined functional material is a combination of bismuth oxide, samarium oxide, and tantalum oxide in a mass ratio of 8:2:0.5.
[0063] Comparative Example 5 A high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material differs from Example 1 in that the combined functional material is a combination of bismuth oxide, samarium oxide, and tantalum oxide in a mass ratio of 4:1:4.5.
[0064] Performance Evaluation (1) R25 is the resistance value measured by the resistance tester at 25℃ with a test accuracy of ±0.02℃.
[0065] (2) B value: B value = (T1×T2 / (T2-T1))×log(R1 / R2); In the formula: T1 / T2 is 25 / 50; R1 is the resistance value at temperature T1 (25℃); R2 is the resistance value at temperature T2 (50℃); T1 is 298.15K (273.15+25℃); T2 is 323.15K (273.15+50℃).
[0066] (3) High temperature reliability: The oven was used for testing. The ambient temperature was 125℃±5℃ for 1000±24h. After the 1000H test was completed, the R25, 50 and B values were retested after 2h of recovery at normal temperature and humidity. The change rate of R25 and B values was taken and the average of the 6 test results was recorded in Table 1.
[0067] (4) Low temperature reliability: The test was conducted using a low temperature test chamber with an ambient temperature of -40℃±3℃ for a duration of 1000±24h. After the 1000h test was completed, the R25, 50 and B values were retested after 2h of recovery at normal temperature and humidity. The change rate of R25 and B values was taken, and the average of the 6 test results was recorded in Table 1.
[0068] (5) Reliability under constant temperature and humidity: The test is conducted using a constant temperature and humidity test chamber. The thermistor should be kept at 85℃±2℃ and 85%±2% humidity for 1000±24h. After the 1000H test is completed, it should be restored at normal temperature and humidity for 2h, and then the R25, 50 and B values should be retested. The change rate of R25 and B values should be taken, and the average of the 6 test results should be recorded in Table 1.
[0069] (6) Thermal shock reliability: The thermal shock test was conducted using a thermal shock tester. The test was repeated 100 times in air from -40℃±2℃×30min±0.5min to 125℃±5℃×30min±0.5min. After the test, the R25, 50 and B values were remeasured after 2 hours of recovery at normal temperature and humidity. The change rate of R25 and B values was recorded, and the average of the 6 test results was recorded in Table 1.
[0070] Table 1 Performance Evaluation 1
[0071] Table 2 Performance Evaluation 2
[0072] Table 3 Performance Evaluation 3
[0073] The test results above show that Examples 1-3 achieved superior performance compared to Comparative Examples 1-5. Examples 1-3 demonstrated excellent reliability of the thermistor material, good consistency, and exceptional stability. This is mainly due to the technical solutions specified in this application adopted in Examples 1-3. The appropriate formulation achieves a balance between low resistance and high B-value through the synergistic effect of multiple dopant elements. Furthermore, the introduction of a composite agent with specific raw material ratios promotes intergranular material migration and ceramic densification, increases the activation energy required for copper ion valence state transitions and vacancy migration, and suppresses the directional drift of mobile ions on a long scale. Thus, without affecting the main electrical properties, the material's ability to resist performance degradation under thermal and electrical stress is significantly enhanced, resulting in excellent multi-environment reliability.
[0074] Comparative Examples 1-5, because they use technical solutions different from those specified in this application, have significantly weakened the effect of their raw materials in the system, which ultimately leads to a decrease in the overall reliability of the product. Their reliability and comprehensive application performance are significantly worse than those of Examples 1-3.
Claims
1. A highly stable, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material, characterized in that: By mass percentage, the raw material scheme includes: 8-22% manganese tetroxide, 18-37% nickel oxide, 7-22% reinforcing material, 0.1-1% lanthanum trioxide, 1.5-4% combined functional material, and cobalt tetroxide to make up the balance to 100%; The reinforcing material is a combination of nano-copper oxide and nano-zinc oxide, with a mass ratio of (1.5~4.5):(7.5~13). The combined functional material is a combination of bismuth oxide, samarium oxide and tantalum oxide, with a mass ratio of (5~7):(1.5~3):(0.8~1.4).
2. The high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to claim 1, characterized in that: The mass ratio of manganese tetroxide, nickel oxide and lanthanum trioxide is (12~20):(28~36):(0.1~0.45).
3. The high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to claim 2, characterized in that: The D50 particle size of the manganese tetroxide is 1~3μm; the D50 particle size of the nickel oxide is 1.5~2.5μm.
4. The high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to claim 3, characterized in that: The D50 particle size of the nano-copper oxide is 30~80nm; the D50 particle size of the nano-zinc oxide is 20~60nm.
5. The high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to claim 4, characterized in that: The mass ratio of manganese tetroxide, reinforcing material, and combined functional material is (12~20):(9.5~15.5):(1.5~3.5).
6. The high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to claim 5, characterized in that: The D50 particle size of the lanthanum trioxide is 2~5μm.
7. The high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to claim 6, characterized in that: The bismuth oxide has a D50 particle size of 1~5μm; the samarium oxide has a D50 particle size of 1~3μm.
8. The high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to claim 7, characterized in that: The D50 particle size of the tantalum oxide is 0.5~2μm.
9. The high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to claim 8, characterized in that: The D50 particle size of the cobalt tetroxide is 0.8~2.5μm.
10. A method for preparing a high-stability, rare-earth-containing, six-component, low-resistivity, high-B-value NTC thermistor ceramic material according to any one of claims 1 to 9, characterized in that: Specifically, the following steps are included: S1: All weighed raw materials are put into a high-speed pulverizer for dry grinding. The ground and mixed powder is placed in a sagger and pre-fired in air at a temperature of 900~1100℃. S2: The pre-fired powder is poured into a planetary ball mill and wet-milled with deionized water as the grinding medium. After ball milling, the powder is dried to obtain ceramic powder. S3: The dried ceramic powder is filled into a mold and pre-pressed with a dry press to obtain a blank. The blank is then placed in a rubber sleeve, vacuum-sealed, and placed in a cold isostatic press to obtain an ingot. S4: The ingot is placed in a high-temperature sintering furnace and fired at a temperature of 1100~1300℃. After cooling to room temperature in the furnace, a sintered block is obtained. The sintered block is cut into thin slices using a precision inner circle cutter. Both sides of the thin slices are evenly coated with silver electrode paste and placed in a roller kiln for silver firing. After completion, the thin slices are cut into slices according to specifications using a precision dicing machine to obtain NTC thermistor ceramic material.
Citation Information
Patent Citations
Ceramic material, component, and method for producing the component
CN109843828A
Low-temperature sintered NTC thermosensitive resistor ceramic material and preparation method thereof
CN111116173A